2020
DOI: 10.1111/jfpp.14357
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive properties and phenolic compounds in bud, sprout, and fruit ofCapparisspp. plants

Abstract: In this study, changes in bioactive properties and phenolic compounds of different caper parts were reported. Total phenolic contents of C. ovata and C. spinosa plants varied between 175.35 mgGAE/100 g (fruit) and 518.4 mgGAE/100 g (small bud) to 143.58 mgGAE/100 g (fruit and 597.57 mgGAE/100 g (small bud), respectively. While total flavonoid contents of C. ovata parts vary between 9.12 mg/g (fruit) and 37.22 mg/g (small bud), total flavonoid contents of C. spinosa parts changed between 7.43 mg/g (fruit) and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…Ghafoor et al. (2020) reported that TPC of C. ovata and C. spinosa fruit were 175.35 mg GAE/100 g and 143.58 mg GAE/100 g, respectively. Durmaz et al.…”
Section: Resultsmentioning
confidence: 99%
“…Ghafoor et al. (2020) reported that TPC of C. ovata and C. spinosa fruit were 175.35 mg GAE/100 g and 143.58 mg GAE/100 g, respectively. Durmaz et al.…”
Section: Resultsmentioning
confidence: 99%
“…To extract phytochemicals, solvent extraction was the most used method (Ghafoor et al., 2020; Knez Hrnčič, Ivanovski, Cör, & Knez, 2020; Masondo, Stafford, Aremu, & Makunga, 2019; Tormena, Marcheafave, Rakocevic, Bruns, & Scarminio, 2019). In this regard, solvent properties present certainly the key role in phytochemical extraction.…”
Section: Introductionmentioning
confidence: 99%
“…By all, the total phenolic content (including phenolic acids, flavonoids, and coumarins) of the plant seeds ranged from 1.31 mg gallic acid equivalents per g of dry residue (GAE/g DR) to 8.14 mg GAE/g DR (Tlili et al, 2015). Leaves content in phenolic acids corresponded to 427.27 mg GAE/g DR (Mansour et al, 2016) while fruits carry 1.43 mg GAE/g DR and small buds, 5.97 mg GAE/g DR (Ghafoor et al, 2020). Nonetheless, the content of a plant extract in phenolic compounds could be drastically affected by fermentation (Sonmezdag et al, 2019).…”
Section: Phenolic Acids and Fatty Acidsmentioning
confidence: 99%